ENTREPRENEURSHIP ORIENTATION, ORGANIZATIONAL LEARNING AND INNOVATION PERFORMANCE (STUDIES ON SMEs IN WEST JAVA) - Yusron, Achmad (Journal of Islamic enterpreneurship and Management, 2022)
Organizational learning is a learning activity in organizational processes through interaction with the environment that encourages organizations to better integrate knowledge. Through a series of strategies, the development of organizational learning needs to be done to provide a competitive advantage for the organization. This study offers the concept of organizational learning as mediating the relationship between entrepreneurial orientation and innovation performance in online businesses in West Java. In addition, this study aims to analyze the constructs used to build innovation. The sample of this research is 185 MSME owners in West Java. Quantitative studies were selected using the Structural Equational Modeling (SEM) analysis tool. The results of this study indicate that organizational learning is able to bridge the research gap between entrepreneurial orientation and innovation performance. The findings of this study prove empirically that entrepreneurial orientation through learning organizations can maximize the results of innovation performance in online businesses in West Java. This research is limited to online-based small and medium enterprises in West Java.